2005
DOI: 10.1007/s10067-005-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's disease in Lebanon: clinical profile, severity and two-decade comparison

Abstract: The aim of this study is to describe the clinical features of Lebanese patients with Behçet's disease (BD) followed up at a tertiary care center in Lebanon. A retrospective review of medical records of 90 patients who fulfilled the International Study Group (ISG) criteria for diagnosis was performed. The clinical characteristics and severity score were compared with those reported from other populations of Arab and of Turkish origin using the same diagnostic criteria, and a comparison over two decades for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…[37, 38]. Assuming that the reports of Gül et al [8, 9] indicate that FVL and FII 20210A mutations are genetically associated with BD and act synergistically with the tenderness of BD for thrombotic events, one could say that this is one reason that explains why the prevalence of vascular BD is lower in Japan ( p = 6%) [32] and higher in Turkey ( p = 14.3–26%) [29, 30] and in Lebanon ( p = 36.8%) [39]. Consequently, we should expect that this correlation applies in Italy and in Spain as well, where FVL and FII 20210A mutations are also frequently encountered; nevertheless, the studies from Silingardi et al [10] and Espinosa et al [40] did not find such a positive association between those thrombophilic mutations and BD in Italian and Spanish patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[37, 38]. Assuming that the reports of Gül et al [8, 9] indicate that FVL and FII 20210A mutations are genetically associated with BD and act synergistically with the tenderness of BD for thrombotic events, one could say that this is one reason that explains why the prevalence of vascular BD is lower in Japan ( p = 6%) [32] and higher in Turkey ( p = 14.3–26%) [29, 30] and in Lebanon ( p = 36.8%) [39]. Consequently, we should expect that this correlation applies in Italy and in Spain as well, where FVL and FII 20210A mutations are also frequently encountered; nevertheless, the studies from Silingardi et al [10] and Espinosa et al [40] did not find such a positive association between those thrombophilic mutations and BD in Italian and Spanish patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicenter survey held in 2009 in Japan, BD was the 5th most frequent diagnosis (3.9 %) among 3,830 newly arrived uveitis patients in 36 university hospitals [ 8 ]. On the other hand, in Turkey, BD remains the most frequent type of uveitis (32 %) among those patients in a multicenter survey [ 2 ]. In other countries, the rate of BD in newly arrived patients with uveitis in referral centers or university hospitals was 8.6 % in Iran [ 9 ], 7.1 % in southern Thailand [ 10 ], 3.5 % in Saudi Arabia [ 11 ], 3.1 % in northeastern Italy [ 12 ], 1.1 % in Switzerland [ 13 ], 0.8 % in California, USA [ 14 ], and 0.3 % in India [ 15 ].…”
Section: Epidemiologymentioning
confidence: 95%
“…Kucukoglu's study [90] revealed that SVT was the most common vascular symptom (53.3 %), followed by deep vein thrombosis (29.8 %) and arterial lesions (3.6 %). In the literature, venous thrombosis had been reported in 2-26 % of patients with BD [81][82][83][84][85][86]. Ames's study revealed that the patients with BD suffer from venous occlusions more than any other rheumatologic disease [91].…”
Section: Cardiovascular and Pulmonary Involvement In Groupmentioning
confidence: 96%
“…We checked the references of the initially included articles to identify other potentially relevant studies and subjected them to a similar selection process. The data of eight registry studies which were the most comprehensive epidemiological series about BD from different geographic areas was combined to represent general Behçet population [2,[81][82][83][84][85][86][87]. Ultimately, we aimed to compare general characteristics, pulmonary involvement, arterial involvement and venous involvement in group 1 and group 2.…”
Section: Search Strategymentioning
confidence: 99%